Social Documents : Credit (Relations industrielles / Industrial Relations, 1952)
SummaryThe following text is an English translation by the National Catholic Welfare Conference of the discourse given in the French language by His Holiness Pope Pius XII on October 24, 1951, to delegates from 46 nations attending the International Congress on Credit Questions. In his discourse, the Pontiff discussed the moral and social importance of credit and encouraged its fruitful extension.